2014
DOI: 10.4236/ae.2014.21009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of Chrysomya megacephala populations in Malaysia (Diptera: Calliphoridae)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Relevant population genetic markers for C. megacephala have been explored. COI , COII and ISSR markers differentiated between eastern and western populations of C. megacephala in Malaysia [ 169 ], where orographic barriers occur. This study found less genetic variation between populations than expected (relative to related blow flies), and suggested that it was due to urbanization and intercity transport of flies by human activities [ 169 ].…”
Section: Forensic Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Relevant population genetic markers for C. megacephala have been explored. COI , COII and ISSR markers differentiated between eastern and western populations of C. megacephala in Malaysia [ 169 ], where orographic barriers occur. This study found less genetic variation between populations than expected (relative to related blow flies), and suggested that it was due to urbanization and intercity transport of flies by human activities [ 169 ].…”
Section: Forensic Significancementioning
confidence: 99%
“…COI , COII and ISSR markers differentiated between eastern and western populations of C. megacephala in Malaysia [ 169 ], where orographic barriers occur. This study found less genetic variation between populations than expected (relative to related blow flies), and suggested that it was due to urbanization and intercity transport of flies by human activities [ 169 ]. Amplified fragment length polymorphisms of C. megacephala sampled across Florida and Alabama indicated some spatial differentiation, but also that its genetic diversity was diminished relative to both populations in its native range and populations of native blow flies in the USA [ 59 ].…”
Section: Forensic Significancementioning
confidence: 99%
“…megacephala in Malaysia (5 locations) using COI. Neighbour joining tree based on COI sequence showed two main groups, one branch comprised Penang and Selangor populations while another consisted of Johor, Pahang, and Sabah populations [54]. Including more genes in such analyses could be promising.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Chong et al (2014) suggested that since the Chrysomya genomes tend to be highly repetitive, using the repeat motif as the priming region could create reliable polymorphic loci. These markers would again only be counted if the resulting amplicon was longer than 50 and shorter than 500 base pairs long.…”
Section: Clc Genomics Workhopmentioning
confidence: 99%
“…Using published information on insect microsatellites, I searched for the various motifs that have been successful with C. megacephala as well as other members of the family Calliphoridae (Florin & Gyllenstrand, 2002;He et al, 2007;Torres et al, 2008;Chong et al, 2014;Farncombe et al, 2014). The CLC also uses Primer 3 parameters to determine possible primer pairs, their annealing temperatures, GC content, and self-complementarity.…”
Section: Clc Genomics Workhopmentioning
confidence: 99%